Phantom somatosensory evoked potentials following selective intraneural electrical stimulation in two amputees. Issue 6 (June 2018) - Granata, Giuseppe; Di Iorio, Riccardo; Romanello, Roberto; Iodice, Francesco; Raspopovic, Stanisa; Petrini, Francesco; Strauss, Ivo; Valle, Giacomo; Stieglitz, Thomas; Čvančara, Paul; Andreu, David; Divoux, Jean-Louis; et al.
Highlights: New generation prosthesis allows somatosensory feedback by implantion of intraneural electrodes. Objective methods to evaluate the real perception of a sensation in the phantom hand are missing. We recorded somatosensory evoked potentials during intraneural stimulation in two amputees. Abstract: Objective: The aim of the paper is to objectively demonstrate that amputees implanted with intraneural interfaces are truly able to feel a sensation in the phantom hand by recording "phantom" somatosensory evoked potentials from the corresponding brain areas. Methods: We implanted four transverse intrafascicular multichannel electrodes, available with percutaneous connections to a multichannel electrical stimulator, in the median and ulnar nerves of two left trans-radial amputees. Two channels of the implants that were able to elicit sensations during intraneural nerve stimulation were chosen, in both patients, for recording somatosensory evoked potentials. Results: We recorded reproducible evoked responses by stimulating the median and the ulnar nerves in both cases. Latencies were in accordance with the arrival of somatosensory information to the primary somatosensory cortex. Conclusion: Our results provide evidence that sensations generated by intraneural stimulation are truly perceived by amputees and located in the phantom hand. Moreover, our results strongly suggest that sensations perceived in different parts of the phantom hand result in different evoked responses. Significance: Somatosensory evoked potentials obtained by selective intraneural electrical stimulation in amputee patients are a useful tool to provide an objective demonstration of somatosensory feedback in new generation bidirectional prostheses.